PENANAMAN KARAKTER KEWIRAUSAHAAN DI PESANTREN TEBUIRENG - Moch. Choirus Sholeh; Haris Supratno (STAI Pelabuhan Ratu, 2023)
Tebuireng Islamic Boarding School, renowned for its diverse business units, serves as a cornerstone for the institution's economy. Researchers seek to comprehend the entrepreneurial education culture at Tebuireng Islamic Boarding School, encompassing three research focuses: Entrepreneurship, character development, and obstacles to entrepreneurship. This research aims to understand how the boarding school utilizes Islamic values and local wisdom to support entrepreneurial education. The research method employs qualitative descriptive with a case study approach. Data are collected through three techniques: (1) interviews, (2) observations, and (3) documentation. Data analysis involves several stages, including data reduction, data presentation, and drawing conclusions. The research findings are as follows: (1) Business units within Tebuireng provide opportunities for interested students to engage in entrepreneurship, such as cooperatives, publishing, and catering. (2) Tebuireng instills five fundamental values: sincerity, honesty, responsibility, hard work, and tolerance, with three of them being crucial for entrepreneurship: honesty, responsibility, and hard work. These values are instilled through activities like religious studies, motivation sessions, lectures, and other school activities. (3) Supportive factors for cultivating entrepreneurial character at Tebuireng include comprehensive facilities. On the contrary, hindering factors involve restrictions for students still in school to engage in entrepreneurial activities, as well as students' indifference and reluctance.